Plasma cell balanitis: clinical and histopathological features--response to circumcision. Issue 1 (February 1995) - Kumar, B; Sharma, R; Rajagopalan, M; Radotra, B D
Abstract : OBJECTIVE--To evaluate the clinicopathological features and response to circumcision in patients with plasma cell balanitis. SUBJECTS AND METHOD--32 uncircumcised men with penile lesions typical of plasma cell balanitis. Twenty specimens were available for histopathology. RESULTS--Lesions involved prepuce and glans in 17, prepuce only in 10 and in 5 were localised to glans alone or extended to coronal sulcus. Histopathology showed variable features but were consistent with the diagnosis of plasma cell balanitis. Haemosiderin pigment could be detected in only three specimens of patients with shorter duration of the disease. Twenty seven patients were treated with circumcision and no recurrence was noticed in 3 years of follow up. CONCLUSION--Circumcision is an effective treatment modality in plasma cell balanitis. Absence of haemosiderin pigment in majority of tissue sections is difficult to explain but may be related to longer duration of the disease.